Sputum induction and its diagnostic applications in inflammatory airway disorders: a review - Goncalves, Beatriz; Eze, Ukpai A. (Frontiers in Allergy, 2023)
Sputum induction is a technique that covers the induction and the subsequent processing of the expectorate primarily for the analysis of cells and different inflammatory biomarkers present in the airways to further understand the pathophysiology of different inflammatory respiratory disorders such as asthma and COPD as well as the diagnosis of lung diseases like lung cancer, tuberculosis, and Pneumocystis jirovecii pneumonia. Sputum induction is a non-invasive, safe, cost-effective and reliable technique with a high success rate. However, due to being technically demanding, requiring trained staff and time consuming, this technique is only used in restricted research centres and in limited centres of clinical use. When sputum is collected after induction, the primary goal is to obtain a differential cell count and evaluate the molecular biomarkers of airways inflammation which play significant roles in understanding the pathophysiology of inflammatory airways diseases. This technique nowadays can be used further by performing an additional analysis such as flow cytometry and in situ hybridisation on the sputum supernatant to investigate more in depth the immune response and pathophysiological process of the various respiratory diseases. In addition, the application of sputum fluid phase to assess biomarkers could be used more routinely in pathology laboratories for the diagnosis of lung cancer, COPD and asthma as well as for monitoring lung cancer progression, and asthma and COPD treatment, allowing for early detection and a better treatment provided by the clinicians.